Supressão da Sincronização de Disparos Neuronais em Aglomerados de Redes Livres de Escala - Lameu, Ewandson Luiz (2013)
Functional brain networks are composed of cortical areas that are anatomically and functionally connected. One of the cortical networks for which more information is available in the literature is the cat cerebral cortex. Statistical analyses of the latter suggest that its structure can be described as a clustered network, in which each cluster is a scale-free network possessing highly connected hubs. Those hubs are strongly connected together. We have built a clustered scale-free network inspired in the cat and human cortex structure so as to study their dynamical properties. We focus on the synchronization of bursting activity of the cortical areas and how it can be suppressed by means of neuron deactivation through suitably applied light pulses. We show that is possible to effectively suppress bursting synchronization by acting on a single hub, because it is highly connected and have a strong influence over the network.